Opportunities to improve the adoption of health-related quality of life evidence as part of the French Health Technology Assessment process - Hugo Larose; Myrto Lee; Jens Grueger; Amélie Anota; Nicolas Naïditch; Bruno Falissard; Mario Di Palma; Olivier Chassany; Laura Khalfallah-Neelz; Sarah Palazuelos-Muñoz; Aymeric Tetafort (Health Research Policy and Systems, 2023)
Abstract Objectives Patient’s health-related quality of life (HRQoL) is an important outcome measure that is considered by many payers and health technology assessment (HTA) bodies in the evaluation of treatments. We aimed to identify opportunities for HRQoL to be further incorporated into the assessment of the French HTA by comparing three health systems. We put forward recommendations that could bring further innovations to French patients. Methods We reviewed methodologies by the French, German and British HTA, and conducted a systematic review of all French (n = 312) and German (n = 175) HTA appraisals from 01 January 2019 to 31 December 2021. We also setup an advisory board of 11 ex-HTA leaders, payers, methodologists, healthcare providers and patient advocates, from France, Britain and Germany, to discuss opportunities to improve acceptance and adoption of HRQoL evidence in France. Results Our systematic review of HTA appraisals showed a higher HRQoL data rejection rate in France: in > 75% of cases the HRQoL evidence submitted was not accepted for the assessment (usually for methodological reasons, for example, data being considered exploratory; 16–75% of the appraisals mentioned HRQoL evidence, varying by therapeutic area). Overall, we found the French HTA to be more restrictive in its approach than IQWiG. Conclusions Based on these findings we articulate collaborative proposals for industry and the HAS to improve acceptance of HRQoL evidence and create a positive feedback loop between HAS and industry along four dimensions (1) patient perception, (2) testing hierarchy, (3) trial design and (4) data collection.